2014
DOI: 10.3329/fmcj.v8i2.20372
|View full text |Cite
|
Sign up to set email alerts
|

"Nonunion of Adult Humerus Fracture" - Management Using the Ilizarov External Fixator.

Abstract: :Humeral shaft fractures occur about three percent of all fractures in adults. A very high union rate is achieved with non-operative treatment, however when nonunion occurs conservative approach or after operative management they are often very difficult to treat, and often requires multiple procedures to achieve union. Even with multiple procedures, true pseudoarthrosis have only a 59% union rate. The aim of this study was to find out the results of such complicated cases treating with Ilizarov's external fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Union rates from 40% up to 100% have been achieved in treatments with intramedullary nailing (15)(16)(17), with union times ranging between 4.2 to 6 months (15,17,18). Successful results of up to 100% and union times ranging from 5.5-7.2 months have been reported with treatment using the Ilizarov external fixator (13,(19)(20)(21). When using plates to treat nonunion, single-plate and doubleplate methods are performed.…”
Section: Discussionmentioning
confidence: 99%
“…Union rates from 40% up to 100% have been achieved in treatments with intramedullary nailing (15)(16)(17), with union times ranging between 4.2 to 6 months (15,17,18). Successful results of up to 100% and union times ranging from 5.5-7.2 months have been reported with treatment using the Ilizarov external fixator (13,(19)(20)(21). When using plates to treat nonunion, single-plate and doubleplate methods are performed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to the results of many studies that explored the main causes of union failure after surgical treatment of humeral fractures and revealed that carrying weight and appropriate axial rotation movements are essential in bone healing of humerus [15][16][17] . Mid-shaft humeral fractures had high rates of non-union 29 that needs adjuvant physiotherapeutic techniques added to optimum surgical intervention to acquire better outcomes 30 . Absence of complete bone reduction, absence of stable and rigid fixation in addition to high muscular load on humerus was the main reasons for late healing 17.…”
Section: Outcome Of Fixationmentioning
confidence: 99%